Whole Egg Consumption in Zucker Diabetic Fatty Rats Display a Dose-dependent Reduction in Weight Gain and Total Body Fat, Accompanied by an Increase in Lean Body Mass (P21-054-19). (13th June 2019) - Webb, Joe; Saande, Cassondra; Schalinske, Kevin; Rowling, Matthew
Abstract: Objectives: The objective of this study was to determine the lowest dose of whole egg-based diets to effectively attenuate the obese phenotype in type 2 diabetic (T2D) rats using a dose-response experimental design. Methods: Male Zucker diabetic fatty (ZDF) rats ( n = 8) and their lean controls ( n = 8) were obtained at 6 weeks of age. Following one week of acclimation, animals were randomly assigned to one of 5 treatment groups: a casein-based diet (20% protein, w/w) or a whole-egg based diet provided at either 20, 10, 5, or 2.5% egg protein (w/w). Animals were fed their respective diets for 8 weeks with weight gain and food intake measured daily. At 14 weeks of age, body composition was analyzed by dual X-ray absorptiometry and statistical differences were measured between groups using a 2-way ANOVA at P < 0.05. Results: Whole egg-based diets exerted a dose-dependent decrease in cumulative body weight gain and final body weight; increased in food intake; decreased total body fat; and increased lean body mass. Interestingly, the 20% whole egg protein diet decreased body fat and increased lean body mass in the ZDF rats and their lean controls. Conclusions: Together, these data support the hypothesis that dietary consumption of whole eggs may decrease weight gain, reduce body fat, and increase lean body mass in a dose-dependent manner in ZDF rats. These results suggest the need to modify dietary recommendations during T2D and obesity to potentially consume more whole egg. Funding Sources: This work was supported by the Egg Nutrition Center and in part by a National Science Foundation Graduate Research Fellowship. Supporting Tables, Images and/or Graphs: